ANALISIS KEMAMPUAN MENYUSUN BAHAN AJAR MENGGUNAKAN APLIKASI CANVA PADA MAHASISWA PROGRAM STUDI S1 PGSD - halidjah, siti (JURNAL PENDIDIKAN DASAR, 2024)
Abstract: The purpose of this study is to describe the ability to compile teaching materials using the Canva application in students of the S1 PGSD Study Program. The subject of the study is a student of the 2021 micro learning group. The data source is in the form of teaching materials documents prepared by students. The research process begins with the planning stage, implementation, followed by data analysis, and ends with reporting. The data collection technique uses document studies with the collection tool in the form of teaching material documents prepared by students. Data analysis follows the flow of collection, reduction, presentation, and conclusion. The results of the study showed that students' ability to compile teaching materials using the Canva application was in the "Good" criterion with an average score of 80.09. Keywords: teaching materials, canva app Abstrak: Tujuan dilaksanakannnya penelitian ini untuk mendeskripsikan kemampuan menyusun bahan ajar menggunakan aplikasi canva pada mahasiswa Program Studi S1 PGSD. Subjek penelitian adalah mahasiswa kelompok pembelajaran mikro Angkatan 2021. Sumber data berupa dokumen bahan ajar yang disusun mahasiswa. Prosesur penelitian dimulai dengan tahap perencanaan, pelaksanaan, dilanjutkan dengan analisis data, dan diakhiri dengan pelaporan. Teknik pengumpulan data menggunakan studi dokumen dengan alat pengumpulnya berupa dokumen bahan ajar yang disusun mahasiswa. Analisis data mengikuti alur pengumpulan, reduksi, penyajian, dan penyimpulan. Hasil dari penelitian didapat bahwa kemampuan mahasiswa dalam menyusun bahan ajar menggunakan aplikasi canva berada di kriteria “Baik” dengan rata-rata nilai 80,09. Kata Kunci: bahan ajar, aplikasi canva